A Status Update on Fiscal Exit Strategies. (IMF Working Papers; Working Paper ;, 2010)
With a modest recovery in the global economy underway, and amid rising concerns about the sharp increase in government debt in several countries, debate has increasingly focused on the need to identify and implement fiscal exit strategies. This paper reviews the medium-term plans of 25 countries - the G20 plus six others with large adjustment needs - and finds that most of them have made reasonable progress in defining these strategies. Nevertheless, strategies fall short in some areas, including committing to long-term debt targets, spelling out adjustment measures in detail, and tackling rising health care costs.